Effects of Estradiol Dose and Serum Estradiol Levels on Metabolic Measures in Early and Late Postmenopausal Women in the REPLENISH Trial - Intira Sriprasert (2020)
© Copyright 2020, Mary Ann Liebert, Inc., publishers 2020. To identify the association of estradiol (E2) dose and serum E2 levels with metabolic measures in early (<6 years) compared with late (≥10 years) postmenopausal women from the REPLENISH trial. Material and Methods: This is a post hoc analysis of a multicenter randomized clinical trial in the United States. Four doses of TX-001HR, an oral combination of E2 and progesterone (P4), and placebo were tested. This analysis included a total of 1,216 early and 297 late postmenopausal women. Linear mixed-effects models tested the association of E2 dose and serum E2 levels with changes in metabolic parameters; total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglyceride (TG), and glucose (GLUC) levels from six visits over 12 months, adjusted for the serum P4 level. Results: A higher E2 dose was significantly associated with lower TC (p = 0.02) and LDL-C (p = 0.002) and higher HDL-C (p = 0.04) levels in early, but not late, postmenopause. With longer time since menopause, the inverse association of E2 dose with TC and LDL-C and positive association with HDL-C were attenuated (interaction p < 0.05). Higher serum E2 levels were significantly associated with lower TC (p = 0.004), LDL-C (p = 0.0001), and fasting blood GLUC (p = 0.003) and higher TG (p = 0.002) levels in early postmenopause. Conclusion: E2 dose differentially affects metabolic measures among early compared with late postmenopausal women. No significant main effect of the serum P4 level was found. As the metabolic parameters studied are risk factors for cardiovascular events, these results support the timing hypothesis of E2 therapy and its cardiovascular benefits.